2021
DOI: 10.1177/1066480721992504
|View full text |Cite
|
Sign up to set email alerts
|

Disability-Responsive Adaptations: Child–Parent–Relationship Therapy for Children With Disabilities

Abstract: Children with disabilities have unique and often specialized needs. The parents of children with disabilities play an integral and sometimes challenging role in supporting, advocating, and caring for their children. This article introduces an evidence-based approach to work with parents of children with disabilities that focuses on strengthening the relationship between the parent and child through child–parent–relationship therapy (CPRT). Disability-responsive adaptations and recommendations are provided for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…It can be concluded that children need to learn various skills in early childhood for their subsequent educational and social success (Nakamichi et al, 2021). Parents’ behavior toward their children can affect children’s developmental processes (Aydin & Yamac, 2014; Rodríguez et al, 2021). Parents of deaf children may have difficulty controlling and managing their behaviors and emotions (Wake & Carew, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be concluded that children need to learn various skills in early childhood for their subsequent educational and social success (Nakamichi et al, 2021). Parents’ behavior toward their children can affect children’s developmental processes (Aydin & Yamac, 2014; Rodríguez et al, 2021). Parents of deaf children may have difficulty controlling and managing their behaviors and emotions (Wake & Carew, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Mothers of deaf children need particular interventions to improve their emotion regulation (Ashori & Jalil-Abkenar, 2021). Child–parent relationship therapy (CPRT) is an evidence-based method for working with parents of children with specific problems that focuses on improving the interaction between the child and parent (Rodríguez et al, 2021). CPRT emphasizes enhancing child–parent attachment and reducing parenting stress (Lin & Bratton, 2015).…”
Section: Emotion Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, scholars have conducted CPRT research with a variety of presenting concerns, including with single parents (Bratton & Landreth, 1995; Johnson, 2014), conservative Christian parents (Bornsheuer-Boswell et al, 2013), adoptive parents (Opiola & Bratton, 2018; Swan et al, 2019), and with low-income families (Ceballos & Bratton, 2010; Sheely & Bratton, 2010; Socarras et al, 2015). Additionally, researchers have utilized CPRT with diverse populations, including Latino families (Ceballos & Bratton, 2010; Hassey et al, 2017) and African American families (Sheely & Bratton, 2010; Socarras et al, 2015), and was conceptualized for use with parents of children with disabilities (Rodríguez et al, 2021). The following section outlines the CPRT procedures (Landreth & Bratton, 2019) and the specific play session skills taught for each week of the intervention.…”
Section: Ccptmentioning
confidence: 99%